3D printing individualized triboelectric nanogenerator with macro-pattern. (August 2018) - Qiao, Haiyu; Zhang, Yun; Huang, Zhigao; Wang, Yunming; Li, Dequn; Zhou, Huamin
Abstract: Triboelectric nanogenerator (TENG) is one of the most attractive candidates for providing a green energy source capable of satisfying the world's energy consumption. 3D printing is a promising route to satisfy the demands of various self-powered devices with individualized design in practical applications such as signal processing, precisely tuning circuits, active sensor networks, remote controls, and flexible electronics. This work reports an approach of fused deposition modeling (FDM), one of 3D printing methods, which enables the creation of optimized digital designs for TENG devices for the purpose of efficiently harvesting ambient vibration energy. To obtain satisfying output power and high mechanical energy conversion efficiency, various positive and negative polymers were chosen as friction layers, such as polylactic acid (PLA), nylon (PA), a mixture of polypropylene and polyethylene (PP/PE), and poly(ethylene terephthalateco-1, 4-cylclohexylenedimethylene terephthalate) (PETG). By increasing the vibrational frequency from 5 Hz to 20 Hz, the output voltage of the TENG device increased from 50 V to 241 V in a TENG device using nylon (PA) and a mixture of polypropylene and polyethylene (PP/PE). The TENG device had a 0° contact angle between the two films, which also had some macroscopic patterns on their surfaces. Simultaneously, a decrease in the filling rate (from 100% to 20%) and thickness (from 0.4 to 0.2 mm) resulted in an increase in the output voltage from 57 V to 176 V and from 50 V to 241 V, respectively. To better understand the effects of the printing parameters on the output performance, we studied the factors of the filling rate, thickness, contact angle and the width of the zigzag pattern. From these results, we conclude that 3D printing based on the FDM strategy to fabricate TENG outstandingly improves the output performance by decreasing the effective Young's modulus. Additionally, the peak of the current reaches 1.52 mA in ultrashort time. The triboelectrification efficiency in this vertical contact-separation mode reaches 63.9%. Our concept of 3D printing based on FDM will stimulate further fundamental work in fabricating approaches to harvesting environmental energy. Graphical abstract: To achieve the self-powered devices with individualized design in practical applications, this work reports an approach, 3D printing based on fused deposition modeling (FDM), which enables optimally digital designs of TENG device by efficiently harvesting ambient vibration energy. To further obtain satisfying output power and high mechanical energy conversion efficiency, we study the effect of filling rates, contact angles, widths of the zigzag pattern, excitation frequencies, input power and choice of materials on the output voltage of the TENG. The energy conversion efficiency of this vertical contact-separation mode reaches 63.9%. The maximum output voltage reaches 241 V and the current is 1.52 mA at 20 Hz. fx1 Highlights: 3D printing directly fabricated the individualized TENG based on the digital designs. The positive/negative polymers as friction layers of TENG are chose to improve output power and energy conversion efficiency. The macrostructure of friction electrodes has been studied, including filling rates, contact angles and macro pattern. The η of the TENG reaches 63.9% (U = 241V, I = 1.52 mA) at 20 Hz.